Complications and outcomes of hospitalizations for patients with and without Parkinson disease - George, Benjamin P.; Barbosa, William A.; Sethi, Anish; Richard, Irene H. (Frontiers in Aging Neuroscience, 2023)
Objective To examine complications and outcomes of hospitalizations for common indications for hospitalization among patients with Parkinson disease (PD). Methods We identified and selected the ten most common indications for hospitalization among individuals ≥65 years of age using principal diagnoses from the California State Inpatient Database, 2018–2020. Patients with comorbid PD were identified using secondary diagnosis codes and matched one-to-one to patients without PD based on principal diagnosis (exact matching), age, gender, race and ethnicity, and Elixhauser comorbidity index (coarsened exact matching). We identified potentially preventable complications based on the absence of present on admission indicators among secondary diagnoses. In the matched cohort, we compared inpatient complications, early Do-Not-Resuscitate (DNR) orders (placed within 24 h of admission), use of life-sustaining therapies, new nursing facility requirement on discharge, and death or hospice discharge for patients with and without PD. Results We identified 35,457 patients with PD among the ten leading indications for hospitalization in older adults who were matched one-to-one to patients without PD (n = 70,914 in total). Comorbid PD was associated with an increased odds of developing aspiration pneumonia (OR 1.17 95% CI 1.02–1.35) and delirium (OR 1.11 95% CI 1.02–1.22) during admission. Patients with PD had greater odds of early DNR orders [placed within 24 h of admission] (OR 1.34 95% CI 1.29–1.39). While there was no difference in the odds of mechanical ventilation (OR 1.04 95% CI 0.98–1.11), patients with PD demonstrated greater odds of tracheostomy (OR 1.41 95% CI 1.12–1.77) and gastrostomy placement (OR 2.00 95% CI 1.82–2.20). PD was associated with greater odds of new nursing facility requirement upon discharge (OR 1.58 95% CI 1.53–1.64). Patients with PD were more likely to die as a result of their hospitalization (OR 1.11 95% CI 1.06–1.16). Conclusion Patients with PD are at greater risk of developing aspiration pneumonia and delirium as a complication of their hospitalization. While patients with PD more often have early DNR orders, they have greater utilization of life-sustaining therapies and experience worse outcomes of their hospitalization including new nursing facility requirement upon discharge and greater mortality.